Learning sets theory using gaple cards: a study of east java ethnomathematics - Almaghfiroh, Violina; Afandy, Muhammad Irfan; Marhayati, Marhayati (Pusat Studi Pengembangan Pembelajaran Matematika, 2023)
Students' interest in learning mathematics in Indonesia still needs to be improved. Efforts can be made by providing creative learning in the classroom, one of which is by linking mathematics and culture, known as ethnomathematics. Ethnomathematics can be used as a learning innovation to motivate students to learn mathematics. Therefore, this study aims to explore the concept of mathematics in one of the traditional game cultures still developing in Malang, East Java, namely Gaple. Gaple cards can be used as a media for learning mathematics in set material linked through the Realistic Mathematics Education (RME) approach. This study used a descriptive qualitative method with an ethnographic approach, which describes the results of the ethnomathematics exploration of the Gaple card game. Data collection uses observation, interviews, literature review, and photo documentation to explore ethnomathematics elements on gaple game cards. Exploration results were obtained by observing the number of points on each gaple card, namely the concept of universal sets, intersections, unions, and complements. These results are then packaged in a table of learning activities by implementing the three stages of the RME approach.